High diagnostic accuracy of automated rapid Strep A test reduces antibiotic prescriptions for children in the United Arab Emirates - Salama Bin Hendi; Zainab A. Malik; Amar Hassan Khamis; Fadil Y. A. Al-Najjar (BMC, 2021)
Abstract Background Diagnosis of Group A Streptococcus (GAS) pharyngitis in children is hindered by variable sensitivity of clinical criteria and rapid Strep A tests (SAT), resulting in reliance on throat cultures as the gold standard for diagnosis. Delays while awaiting culture reports result in unnecessary antibiotic prescriptions among children, contributing to the spread of antimicrobial resistance (AMR). Methods Diagnostic accuracy study of an automated SAT (A-SAT) in children up to 16 years of age presenting to an emergency room with signs and symptoms of pharyngitis between March and June 2019. Paired throat swabs for A-SAT and culture were collected. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for A-SAT were calculated. Results Two hundred and ninety-one children were included in this study. 168 (57.7%) were boys and the mean age was 4.2 years. A-SAT was positive in 94 (32.3%) and throat culture was positive in 90 (30.9%) children. A-SAT and throat culture results showed a high level of consistency in our cohort. Only 6 (2%) children had inconsistent results, demonstrating that the A-SAT has a high sensitivity (98.9%), specificity (97.5%), PPV (94.7%) and NPV (99.5%) for the diagnosis of GAS pharyngitis in children. Only 92 (32%) children were prescribed antibiotics while the vast majority (68%) were not. Conclusions A-SAT is a quick and reliable test with diagnostic accuracy comparable to throat culture. Its widespread clinical use can help limit antibiotic prescriptions to children presenting with pharyngitis, thus limiting the spread of AMR.